2008
DOI: 10.1021/jp710757y
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Stability of 1-Butene:  An Electron Momentum Spectroscopy Investigation

Abstract: The valence-shell electron momentum distributions for 1-butene are measured by electron momentum spectroscopy (EMS) employing non-coplanar symmetric geometry. The experimental electron momentum distributions are compared with the density functional theory (DFT) calculations using different-sized basis sets. Although the two conformers of 1-butene in the gas phase, namely the skew and syn, have very close ionization potentials, the electron momentum distributions, especially in the low momentum region, can show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
70
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(81 citation statements)
references
References 60 publications
8
70
2
1
Order By: Relevance
“…Recently 1-butene was measured by electron momentum spectroscopy [9]. From the estimated conformational abundances of 69% for the gauche and 31% for the cis form at room temperature it was concluded that the gauche conformer is the most stable structure, which is in accordance with the conclusion of the microwave study.…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…Recently 1-butene was measured by electron momentum spectroscopy [9]. From the estimated conformational abundances of 69% for the gauche and 31% for the cis form at room temperature it was concluded that the gauche conformer is the most stable structure, which is in accordance with the conclusion of the microwave study.…”
Section: Introductionsupporting
confidence: 74%
“…All previous theoretical calculations [3,4,10,9] predict the energetic preference of the gauche form over the cis one with an energy difference of about 35-200 cm −1 .…”
Section: Introductionmentioning
confidence: 94%
“…When these data are produced satisfactory correlations in multi-regression analysis with σ I, σ R and Swain-Lupton's constants [33]. The generated multi-regression analysis equations are given in (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) …”
Section: Volume 53mentioning
confidence: 99%
“…Proton chemical shifts splitting patterns used for prediction of spatial arrangement of heterocyclic ring protons in cyclohexane and five membered pyrazolines [16]. Correlation analysis was used for studying reaction speeds, structural conformations of alkenes [17], alkynes [18], α,β-unsaturated aldehydes [19], ketones [20], ω-substituted ketones [21] and its esters, halo acyl bromides [22], 1 H pyrazoles [23] and its derivatives. Thirunarayanan and Manikandan have studied the dosage of drug analysis using correlation study [ 24].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous synthetic methods of oxazine derivatives were reported in literature such as solvent-free and solvent-assisted methods [11]. Correlation analysis was useful for prediction of reaction speeds, structural conformations of alkenes [12], alkynes [13], α,β-unsaturated aldehydes [14], ketones [15], ω-substituted ketones [16] and its esters, halo acyl bromides [17], 1H pyrazoles [18] and its derivatives. Infrared spectroscopic frequencies were applied for s-cis and s-trans conformations of ground state equilibrium of unsaturated carbonyl systems with respect to carbonyl and vinyl groups [19].…”
Section: Introductionmentioning
confidence: 99%